DISCOURSE OF CRISIS COMMUNICATIONS: SOCIO-CULTURAL ANALYSIS - Poda, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. Crises of different origins can seriously damage the reputation of authorities and undermine their legitimacy. This is largely due to the widespread use of the Internet, and web 2.0 technologies, in particular social media. Today, it is not the crisis incident itself that plays a key role in social discontent, but the way information about it is communicated. Moreover, the turning point in the transition of an event into a crisis often is not a physical action, but a communicative one. The aim of the study is to establish the peculiarities of the deployment of crisis communications in the modern world. The tasks are to determine the essence of crisis and crisis communications and to identify the main directions of their deployment. Research methodology includes a sociocultural methodological approach, methods of a systematic analysis, comparison, and critical analysis. Research results. Any crisis situation requires the immediate influence of management structures in conditions of increased uncertainty and escalation of events. Crisis phenomena are an integral element of the political process, since politics, as a regulatory and control sphere of society, implies the presence of a constant clash of interests of individuals and large social groups. A crisis situation, acting as a kind of violation of the traditional and usual state of affairs in the political system of society, immediately attracts attention and causes concern on the part of citizens, since a political crisis carries a potential danger to social stability. Crisis communications is an activity aimed at establishing effective interactions between the organization (authority) and society in order to maintain its stable reputation and minimize reputational risks before, during, and after the impact of the crisis. Crisis communications have in their arsenal special crisis (namely, diagnosis, directed forecasting, and crisis management) as well as adaptive technologies. Discussion. Analyzing the activities of mass media in crisis situations, the latter act as a means of operational information, a tool for influencing social consciousness, and a way of controlling social and political behavior. The main principles of effective crisis communication: are the quick provision of information, consistency provided by a unified response, and openness. Conclusions. Crisis management is largely determined by what kind of reality the crisis team createsin the social consciousness through communication. Each crisis situation has a set of unique features, so the choice of a crisis communication model largely depends on the context in which the crisis unfoldsl.